Detection of Viruses in Nasopharyngeal Aspirates of Children Admitted with Lower Respiratory Tract Infections at Hospital Serdang, Selangor, Malaysia - Etemadi, Mohammadreza (2011)
Acute lower respiratory tract infections (ALRTIs) continue to be the most important cause of infant and young children mortality worldwide, most of them occuring in developing countries including Southeast Asia and Africa. The role of viruses as major causative agents of ALRTIs in children is increasingly becoming more evident by using sensitive molecular detection methods. The aim of the study was to assess the epidemiology of respiratory viral infections among children less than five years of ages hospitalized with ALRTIs to the Hospital Serdang using conventional and molecular detection methods and to correlate these findings with demographic and clinical features of the patients in order to determine further common viral atiologic agents. A cross-sectional study was conducted from June until December 2009 among children hospitalized with ALRTI. Nasopharyngeal aspirates were collected from 165 patients based on pre-determined inclusion and exclusion criteria. Direct immunofluorescence assay (DFA) was performed to screen the samples for the presence of respiratory syncytial virus (RSV.), human metapneumovirus (HMPV), parainfluenzavirus 1-3 (PIV1-3), influenza virus type A and B (IFV A & B), and human adenoviruses (HAdV). Negative samples tested by DFA were followed by shell vial culture (SVC), as a supplementary test to enhance the detection of these eight viruses. Viral genomes (RNA/DNA) were extracted and subsequently reverse transcription was done on RNA extracts in order to perform diagnosis using molecular methods. Hemi-nested multiplex RT-PCR was applied for detection of RSV, HMPV, IFV-A and B, PIV 1,2,3, and 4, human rhinoviruses (HRV), human enteroviruses (HEV) and human coronaviruses (HCoV) 229E and OC43. In addition, the presence of human bocavirus (HBoV) and human adenoviruses (HAdV) was investigated separately by nested PCR method. The positive samples using either method were subjected to isolation by cell culture. Vero,HEp-2, HeLa and MRC-5 cell lines were used for isolation of RSV, HAdV and HRV. Selected samples of patients diagnosed with RSV, HRV/HEV, and HAdV were subjected to the sequencing and molecular typing. Mycoplasma serology and bacterial culture were performed on blood samples. At the end of the hospitalization, the children’s hospital chart was reviewed to collect demographic, clinical, laboratory and radiological investigation data using standardized protocol. The association of demographic, clinical features, hematologic factors, radiographic findings, hospital course and severity of disease with infections due to different viruses was studied. Aetiologic agents including virus and/or bacteria were detected in 158 (95.8%) of the patients. Single virus was detected in 114 (67.9%) patients; 46 (27.9%) were coinfected with different viruses including double-virus infections in 37 (22.4%) and triple-virus infections in 9 (5.5%) cases. Approximately 70% of samples were found positive using conventional methods as compared with 96% using molecular methods. A wide range of respiratory viruses was detected in the study. RSV (50.3%), with predominance of group B (GB3 genotype), played a major role among hospitalized children. The results of this survey also showed significant burden of HRV infections (32.7%). Phylogenetic study of the VP4/VP2 region confirmed the broad genetic diversity of circulating HRV. HRV-A strains represented the majority of the detections, 22/36 (61%). Recently discovered HRV-C group was substantially implicated as etiological agent among studied patients, 14/36 (39%). Other etiological agents including HAdV (serotypes 1, 2, 3, and 6), HMPV, IFV-A, PIV 1-3, HBoV, HCoVOC43 and HEV (B, C, and D species) were detected in 14.5, 9.6, 9.1, 4.8, 3.6, 2.4 and 1.8 percent of the samples, respectively. Ninety percent of the cases occurred in children less than 2 years. The majority of RSV infections occurred in children less than six months as compared with other virus groups. However, HRV was mainly detected in the second half of the infancy. The most common clinical presentations of ALRTI, among hospitalized children infected with the studied viruses were cough (96%), fever (85%), rhinorrhea (83%), difficulty in breathing (84%), tachypnea, chest wall crepitations (93%) and recession (80%). Children were admitted after a mean duration of three days. However, it was significantly earlier for HRV (1.9 days) than RSV (4.0days) infections. Fever was a prominent feature of RSV and IFV infections. In this study, HRV-C infected children were more likely to have wheezing/rhonchi as compared with HRV-A. The results of the investigation also showed that antibiotics were administerd in majority of the patients 136/165, (82%). HRV-infected patients were less likely to receive antibiotics compared with RSV patients. The results of thestudy suggested that respiratory viral agents significantly contributed to the aetiology of ALRTIs among hospitalized children. Our results demonstrated the potential usefulness of molecular detection methods compared with conventional methods for the diagnosis of ARTIs among hospitalized children. In this study, newly discovered viruses including HMPV, HBoV and HRV-C were reported for the first time in Malaysia. Our study also highlighted that the epidemiology and clinical features were specified to certain viral agents studied.